Identifikasi Molekuler Pasteurella multocida Penyebab Pasteurellosis Pada Babi Di Yogyakarta - Victor Lenda; Hermilinda Parera (JURNAL KAJIAN VETERINER, 2019)
The purpose of this study was to determine the genetic variation of P.multocida in Yogyakarta with other overseas P. multocida strains. Samples were obtained from necropted intensive pig farming with clinically pneumonia symptoms, specific pulmonary lessions and then followed by histopathological examination and b iochemical characterization of the isolates. Then followed by histopathological examination and biochemical characterization of the isolates. Moleculartest performed by DNA extraction using the QIAGEN QIAamp DNA minikit, amplification of the 16S rRNA gene using forward primer 5' GGA GTG AAC TGC AGC TAA TAC C 3', and reverse primer 5' GTA GGT AAG CTT CGC GTT GTT G 3', electrophoresis, purification and sequencing. Macroscopic and histopathological examination results were analyzed descriptively. Sequencing r esults were analyzed by multiple alignment with other Pasteurella spp. taken from GenBank using the Clustal W software, subsequently analyzed using Neighbour Joining and Maximum Parsimony method that exist in program MEGA version 5.1 The results showed gen etic distance based on 765 nucleotides of 16S rRNA gene of P. multocida isolates from lungs of bronchopneumonia of swine in Yogyakarta at 0%. Filogram based on the nucleotide sequence showed a high similarity between P. multocida isolates from Yogyakarta a nd other isolates from USA, Germany, China, Europe, and Hungaria.